Intra-corporeal delta-shaped anastomosis in laparoscopic right hemicolectomy for right colon cancer: a safe and effective technique. (5th February 2019) - Su, Hao; Jin, Wei-Sen; Wang, Peng; Bao, Mandula; Wang, Xue-Wei; Liu, Qian; Wang, Xi-Shan; Zhou, Zhi-Xiang; Zhou, Hai-Tao
Abstract: Background and objective: Intra-corporeal delta-shaped anastomosis (IDA) is an important development in laparoscopic digestive-tract reconstruction. We applied it in laparoscopic right hemicolectomy for right colon cancer and compared the short-term outcomes between the patients treated with IDA and conventional extracorporeal anastomosis (EA). Methods: Between 1 January 2016 and 1 October 2017, 36 and 50 patients who underwent IDA and EA, respectively, were included. Data on clinicopathological characteristics, surgical outcomes, post-operative recovery and complications were collected and compared between the two groups. Results: Surgical outcomes and clinicopathological characteristics were similar between the two groups except the length of incision, which was significantly shorter in the IDA group than in the EA group (4.6 ± 0.6 vs 5.6 ± 0.7 cm, P  < 0.001). The time to ground activities, fluid diet intake and post-operative hospitalization did not differ between the groups; however, the time to first flatus was significantly shorter in the IDA group than in the EA group (2.8 ± 0.5 vs 3.2 ± 0.8 days, P  = 0.004). The post-operative visual analogue scale for pain was lower in the IDA group than in the EA group on post-operative Day 1 (4.0 ± 0.7 vs 4.5 ± 1.0, P  = 0.002) and post-operative Day 3 (2.7 ± 0.6 vs 3.4 ± 0.6, P  < 0.001). The surgical complication rates were 8.3 and 16.0% in the IDA and EA groups ( P  = 0.470), respectively. No complications such as anastomotic bleeding, stenosis and leakage occurred in any patient. Conclusions: IDA is safe and feasible and shows more satisfactory short-term outcomes than EA.